The relationship of D-Dimer level with various diseases - Eljamay, Salwa Muftah; Marri Younis, Mohammed; Elgebaily, Emad Saleh Mousa (Data Sciences Indonesia (DSI), 2022)
D-dimer is a biomarker of thrombosis considered to predict poor outcomes in patients with various diseases. This study aimed to find out the relationship between levels of D dimer in different diseases. 556 blood sample analyses for D dimer Patients' were collected from private laboratories, isolation, and health care centres in the Derna, Al- Gubba City, and its surrounding areas, Plasma separation from the tube containing sodium citrate, Preparation of I-Chroma D-Dimer Quantitative kits reagent. The Frequency and Percent of the Gender were 278 (50%) for males, 278 (50%) for females and for Chronic Diseases, the highest percent for Pneumonia was 121 (21.8%), followed by Blood Pressure at 77 (13.8 %). Diabetes Miletus 51 (9.2%), and for other diseases 71 (12.8%), the type of infection, the highest percent for Viral Infection was 498 (89.6%), followed by Surgery 23 (4.1%), Deep Vein Thrombosis 18 (3.2%), and for Respiratory Diseases 17 (3.1%), the level of D dimer which the highest percent for Moderate 247 (44.4%), followed by High 149 (26.8%). The result of D dimer was Normal 109 (19.6%), and the very high result of 51 (9.2%), the relationship between D dimer result and chronic disease was the highest for blood pressure followed by pneumonia, diabetes Miletus, Anemia, kidney disease, and Heart disease, The correlation between D dimer for age and chronic diseases, p-value < & = 0.05, and there is not a significant relationship between D dimer and type of infection and gender p-value < 0.05. We concluded that the obtained results prove that among obtained results, there is a strong relationship between age and chronic diseases, an increase in the level of D-dimer, level in the blood is not an indication of a specific disease, but rather a signal and alert for several diseases, many diseases